INTEGRASI VOICE OF COSTUMER DENGAN PRINSIP SYARIAH UNTUK MENYERAP ASPIRASI KONSUMEN MUSLIM - Nabil Ahmad Rasikh; Siti Nuraeni (Gunung Djati Conference Series, 2025)
This article explores how Voice of Customer can be integrated with Islamic values to better capture and respond to the needs of Muslim consumers. In today’s market, Muslim customers are becoming more aware and selective, not only expecting quality and convenience but also demanding ethical, halal-compliant products and services. Voice of Costumer, typically used to gather feedback and improve service quality, must be adapted to consider both functional and spiritual dimensions in a Sharia-based business environment. Through a qualitative, literature-based approach, this study identifies key values such as honesty (sidq), trust (amanah), fairness, and social responsibility as essential in building trust through Voice of Costumer systems. A case study on LinkAja Syariah shows how Islamic branding and customer engagement (known as Customer Citizenship Behaviour) significantly influence user decisions. These findings suggest that when customers are treated as value co-creators and their feedback is aligned with Islamic principles, it can lead to greater loyalty and meaningful brand relationships. Ultimately, integrating Voice of Costumer with Sharia principles not only improves customer satisfaction but also supports the broader goals of Islamic business ethics and the realization of maqāṣid al-syarī‘ah in modern economic activity.